All known and a new dino-age amber classified within seven global forests - Peter Vršanský; Júlia Kotulová; Helena Pálková; Dušan Starek; Silvia Antolíková; Štefan Jósza; Martina Havelcová; Lucia Vršanská; Miroslav Hain; Daniel Peyrot; Jan Hinkelman; Romain Garrouste; et al. (Gondwana Research, 2026)

Lebanese amber: A glimpse into the origins of Recent terrestrial biodiversity - Dany Azar; Sibelle Maksoud (Palaeoworld, 2025)

A new early Barremian fossiliferous amber outcrop at Beqaa Kafra (Northern Lebanon) - Dany Azar; Eduardo Barrón; Denise Iskandar-Tabib; Sibelle Maksoud (Palaeoworld, 2025)

A new genus of aphids from the Bqaatouta outcrop of Lower Cretaceous Lebanese amber (Hemiptera: Tajmyraphidoidea) - Michael S. Engel; Mounir Maalouf; André Nel; Dany Azar (Palaeoworld, 2025)

Xenophlebotomites eliei, a new genus and species of phlebotomine sandflies from Lower Cretaceous Lebanese amber (Diptera: Psychodidae: Phlebotominae) - Dany Azar; Sibelle Maksoud (Palaeoworld, 2025)

New records of barklice (Psocodea, Empheriidae) from the Bqaatouta and Baskinta amber (early Barremian, Early Cretaceous) in Lebanon - Marina Hakim; Mounir Maalouf; Dany Azar (Palaeoworld, 2025)

A new serphitid wasp (Hymenoptera: Serphitidae) from the Early Cretaceous Lebanese amber - Sergio Álvarez-Parra; Alexandr P. Rasnitsyn; Dany Azar (Palaeoworld, 2025)

A new genus of the family Spathiopterygidae (Hymenoptera: Diaprioidea) from mid-Cretaceous Kachin amber - Sergio Álvarez-Parra; Corentin Jouault; Marina Hakim; Dany Azar; Diying Huang (PalZ, 2025)

Unraveling the insect head: Segmentation and pancrustacean homologies - Patricia Nel; Michael S. Engel; Carmen Soriano; Sylvain Pont; Lauriane Jacquelin; Laurence Dollinger; Laure Desutter-Grandcolas; Tony Robillard; Romain Garrouste; Dany Azar; André Nel (Arthropod Structure & Development, 2025)

Discovering a new fossil chironomid from Lower Cretaceous Lebanese Amber: Electroneura pinhoi sp. nov. Amaral, Silva & Baranov (Chironomidae: Tanypodinae) - Fabio Laurindo da Silva; André P. Amaral; Dany Azar; Viktor Baranov (PalZ, 2024)
Here we present new insights into Chironomidae (Insecta, Diptera) preserved in Lower Cretaceous Lebanese amber. We describe a new genus and species, Electroneura pinhoi gen. et sp. nov., seemingly related to Tanypodinae and offer an amended description of Libanopelopia cretacica Veltz, Azar and Nel, 2007. Moreover, our investigation highlights the challenges of assigning fossils to modern taxonomic groups, based on previous studies of Tanypodinae, underscoring the necessity of considering the geological context and utilizing, when possible, both morphological and molecular data from extant taxa to validate taxonomic assignments in paleontological studies.

Amber and the Cretaceous Resinous Interval - Xavier Delclòs; Enrique Peñalver; Eduardo Barrón; David Peris; David A. Grimaldi; Michael Holz; Conrad C. Labandeira; Erin E. Saupe; Christopher R. Scotese; Mónica M. Solórzano-Kraemer; Sergio Álvarez-Parra; Antonio Arillo; et al. (Earth-Science Reviews, 2023)

Jordanian–Lebanese–Syrian cockroaches s.s. from Lower Cretaceous amber – Monograph - Hemen Sendi; Peter Vršanský; Dany Azar (Biologia, 2023)

Mesozoic cockroaches (Insecta: Mesoblattinidae, Blattulidae) from shale and dysodile of Lebanon - Júlia Káčerová; Dany Azar (Biologia, 2022)

Edgellia libanica n. organo-gen., n. organo-sp., a new Dasycladalean organ from the Lower Cretaceous of Lebanon - Sibelle Maksoud; Bruno Granier; Huang Diying; Dany Azar (Arabian Journal of Geosciences, 2021)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: the importance of private collections - Carolin Haug; Jelle W. F. Reumer; Joachim T. Haug; Antonio Arillo; Denis Audo; Dany Azar; Viktor Baranov; Rolf Beutel; Sylvain Charbonnier; Rodney Feldmann; Christian Foth; René H. B. Fraaije; et al. (PalZ, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

First Report of the Ticks Haemaphysalis punctata Canestrini et Fanzago, 1878, Haemaphysalis parva (Neumann, 1897) and Dermacentor marginatus (Sulzer, 1776) (Acari, Amblyommidae) from Humans in Lebanon - Martin Raad; Dany Azar; M. Alejandra Perotti (Acta Parasitologica, 2020)

Parasitic cockroaches indicate complex states of earliest proved ants - Peter Vršanský; Lucia Šmídová; Hemen Sendi; Peter Barna; Patrick Müller; Sieghard Ellenberger; Hao Wu; Xiaoyin Ren; Xiaojie Lei; Dany Azar; Juraj Šurka; Tao Su; et al. (Biologia, 2019)

Triploporella ? edgelli n. sp., a new Dasycladalean alga from the Lower Cretaceous of Lebanon - Sibelle Maksoud; Bruno Granier; Dany Azar (Island Arc, 2017)
The Dasycladalean assemblage of the Jezzinian strata (uppermost Barremian–lowermost Aptian) of Lebanon consists of two organo‐genera and eight genera with eleven species, including eight Triploporellaceae. Although Triploporella marsicana (Praturlon, 1964) was reported by Saint‐Marc from the same interval, it is not found in our material. However, a lookalike, which is herein described as Triploporella ? edgelli n. sp., is identified. This new species has cyst‐containers within the primary segments of its laterals but, because it lacks calcified secondary segments, it is left in open nomenclature.

Preliminary report on a dinosaur tracksite from Lower Cretaceous strata in Mount Lebanon - Raymond Gèze; Isabelle Veltz; Jean-Claude Paicheler; Bruno Granier; Roland Habchi; Dany Azar; Sibelle Maksoud (Arabian Journal of Geosciences, 2016)

The first Mesozoic microwhip scorpion (Palpigradi): a new genus and species in mid-Cretaceous amber from Myanmar - Michael S. Engel; Laura C. V. Breitkreuz; Chenyang Cai; Mabel Alvarado; Dany Azar; Diying Huang (The Science of Nature, 2016)

The genus Leptoconops Skuse (Diptera: Ceratopogonidae) in Early Cretaceous Charentese amber - Joanna Choufani; Dany Azar; Vincent Perrichot; Carmen Soriano; Paul Tafforeau; André Nel (Palaeobiodiversity and Palaeoenvironments, 2011)

Mammalian hairs in Early Cretaceous amber - Romain Vullo; Vincent Girard; Dany Azar; Didier Néraudeau (The Science of Nature, 2010)

First nonavian dinosaur from Lebanon: a brachiosaurid sauropod from the Lower Cretaceous of the Jezzine District - Eric Buffetaut; Dany Azar; André Nel; Kamil Ziadé; Aftim Acra (The Science of Nature, 2006)